Correlation between fear of disease progression and quality-of-life in non-dialysis patients with chronic kidney disease in stages 3-5 - Yun-fei Wang; Yu-yu Zhu; De-guang. Wang (Editorial Department of Journal of Clinical Nephrology, 2024)
Objective To evaluate the influencing factors of fear of disease progression and examine its impact on quality-of-life in non-dialysis patients with chronic kidney disease （CKD） in stages 3-5. Methods From June 2022 to May 2023, 130 non-dialysis CKD patients in stages 3-5 were examined by Fear of Progression Questionnaire-Short Form （FoP-Q-SF） and Mos 36-item short-form health survey （SF-36）. General demographics and clinical related parameters were recorded. Degree of FoP, its influencing factors and correlation with quality-of-life were explored. Results Average score of FoP-Q-SF was （32.84 ± 6.13） and 43.84% of them fulfilled the dysfunctional fear of progression criterion （score≥34）. Multiple stepwise linear regression analysis indicated that age （t = −2.024）, education level （t = −2.690）, emotional state （t = 6.808）, disease stage （t = 2.134） and abnormal calcium & phosphorus metabolism （t = −2.099） were the influencing factors for fear of disease progression （P＜0.05）. Quality-of-life scores of CKD patients were lower than those of Chinese normative scores and quality-of-life was lower. In patients with FoP-Q-SF score equal or greater than 34 points, scores of each dimension of SF-36 scale were significantly lower than those with FoP-Q-SF score ＜34 points （P＜0.05）. A significant negative correlation existed between FoP and quality-of-life in non-dialysis CKD patients in stages 3-5. Conclusion In patients with non-dialysis CKD, fear of disease progression seriously affects their quality-of-life. It is correlated with age, education level, emotional state, disease stage and abnormal calcium & phosphorus metabolism. Physicians should devote greater efforts to health education and social supports.